Wasps from the arboreal vegetation in Gorgona National Natural Park, Colombian Pacific - López, Lorena (2014)
Studies of Colombian Hymenoptera are incipient, fragmented and there is no comprehensive study about its size and composition. We know that the guild of hymenopteran parasitoids is the richest in species and that they are common and abundant in all terrestrial ecosystems, acting as regulators of populations of other insects. Studies in Gorgona National Natural Park have mostly focused on the natural history and identification of Formicidae and Apidae. This work was directed toward the identification of other hymenopteran species associated with its tropical rain forest. In November 2007, 16 trees were sampled by fogging with a biodegradable pyrethroid insecticide applied from 1m above the ground to the canopy. We found 641 individuals (45% identified to subfamily and 28% to genera) from seven superfamilies, 20 families and 118 morphospecies. Chalcidoidea was the most representative superfamily, Eulophidae the most diverse family and Braconidae the numerically dominant family. The sampling efficiency was 71% and 166 species are estimated to exist in the island. Approximately 71% of the estimated species were captured during this study. We report 12 genera new for the island. Rev. Biol. Trop. 62 (Suppl. 1): 307-315. Epub 2014 February 01.